Analysis of Physicochemical Properties of Corn Starch Based Composite Biodegradable Cups Influenced by Ultrasonication Pretreatment of Casting Solutions - , Ankit Kumar Deshmukh; , Gopika Talwar (Archives of Current Research International, 2024)
Biodegradable cup is made using a casting solution which is made up of mixture of corn starch (7%), whey protein concentrate(3%), carboxy methyl cellulose (CMC) (2%), and glycerol (4%). This research work focused on analysing the effect of ultrasonication treatment with varying amplitude levels (0%, 20%, 40%, and 60%) and time durations (0, 1, 2, 4, 8, and 16 minutes) on the casting solution for the preparation of biodegradable cups. The study examined the impact of ultrasonication on physical properties such as viscosity, thickness, density and chemical properties such as solubility in water, opacity of the cups. The viscosity of the casting solution decreased as ultrasonication treatment intensity increased, resulting in a decrease in the thickness of the cups. Higher ultrasonication intensity also led to an increase in solubility of cup samples in water. The density of cups, produced through the application of ultrasonication during the preparation process, exhibited an augmentation with elevated ultrasonication intensity and prolonged treatment duration. Ultrasonication treatment caused a decrease in opacity, resulting in a more transparent cup material. Overall, the findings indicate that ultrasonication may be used to streamline the preparation process while enhancing the physical characteristics of biodegradable cups.